Frontispiece: Chemical Vapor Deposition of Ionic Liquids for the Fabrication of Ionogel Films and Patterns. Issue 49 (24th November 2021) - Obst, Martin; Arnauts, Giel; Cruz, Alexander John; Calderon Gonzalez, Maider; Marcoen, Kristof; Hauffman, Tom; Ameloot, Rob
Abstract : Photolithography In their Communication on page 25668, Rob Ameloot et al. report the fabrication of ionogel films and patterns by chemical vapor deposition of ionic liquids.